Pseudomyxoma Peritonei: A Case Report Diagnosed in a 47-Year-Old Woman with Chronic Pelvic Abdominal Pain and Appendicular Origin: Review of the Literature and Management - Pugin, Francois; Bouquet De Jolinière, Jean; Major, Attila; Khomsi, Fathi; Guillou, Louis; Peter, Mathias; Ben Ali, Nordine; Egger, Bernhard; Feki, Anis (Frontiers in Surgery, 2017)
The authors report a case of pseudomyxoma peritonei with gelatinous peritoneum in a 47-year-old-woman. The main symptom for discovery was a chronic pelvic abdominal pain. This disease is particularly rare. The gelatinous substance is often associated with a malignant ovarian tumor or appendicitis perforated. Today, on the whole, an exploratory laparoscopy allows the diagnosis, realize biopsies and appendectomy. The treatment is essentially surgical. The prognosis depends of grade (1/3) and response to chemotherapy. This case was presented to the tumor board.